Hypertonic saline solution evokes cardiovascular recovery in hemorrhagic rats dependent on GABA A and β-adrenergic transmission in the subfornical organ - da Silva, Amanda Barbosa Coelho; Marques, Stefanne Madalena; Fajemiroye, James O.; Colombari, Eduardo [UNESP]; Xavier, Carlos Henrique; Ferreira-Neto, Marcos Luiz; Naves, Lara Marques; Pedrino, Gustavo Rodrigues (Elsevier, 2025)
Background: Studies have reported the use of a hypertonic saline solution (HSS) for the treatment of hypotensive hemorrhage (HH). Despite the established role of central mechanisms in the cardiovascular recovery induced by HSS during HH, the involvement of the Subfornical Organ (SFO) in these responses remains to be elucidated. The present study evaluated the role of SFO and adrenergic neurotransmission in the nucleus in the cardiovascular responses to HSS infusion in hemorrhagic rats. Methods: Mean arterial pressure (MAP), heart rate (HR), and aortic vascular resistance (AVR) were recorded in Wistar rats. HH was performed through blood withdrawal until a MAP of 60 mmHg was attained. Nanoinjections of saline (NaCl; 0.15 M; control group; n = 7), muscimol (4 mM; GABAergic agonist; muscimol group; n = 7), or propranolol (10 mM; non-selective β-adrenergic blocker; propranolol group; n = 7) in SFO were performed 10 min after the onset of blood withdrawal, followed by HSS infusion (NaCl; 3 M; 1.8 ml∙kg−1) 20 min after the beginning of HH. Results: Hypotension, bradycardia, and aortic vasoconstriction were observed in all groups During HH. Sodium overload reestablished MAP and HR while maintaining aortic vasoconstriction in the control group. Activation of GABA A receptors or β-adrenergic receptor blockade in the SFO prevents HSS-induced recovery of MAP and HR. In addition, maintenance of aortic vasoconstriction induced by HSS infusion was abolished by SFO inhibition. Conclusions: The results suggest that the integrity of SFO neurons and β-adrenergic neurotransmission are essential for cardiovascular recovery promoted by sodium overload in hemorrhagic rats.
Keywords: Blood pressure; Hyperosmolarity; Hypotension; Neurotransmission; β-Adrenergic receptor